Porcine Endogenous Retrovirus (PERV) – Molecular Structure and Replication Strategy in the Context of Retroviral Infection Risk of Human Cells - Łopata, Krzysztof; Wojdas, Emilia; Nowak, Roman; Łopata, Paweł; Mazurek, Urszula (Frontiers in Microbiology, 2018)
The xenotransplantation of porcine tissues may help overcome the shortage of human organs for transplantation. However, there are some concerns about recipient safety because the risk of PERV transmission to human cells remains unknown. Although, to date, no PERV infections have been noted in vivo, the possibility of such infections has been confirmed in vitro. Better understanding of the structure and replication cycle of PERVs is a prerequisite for determining the risk of infection and planning PERV-detection strategies. This review presents the current state of knowledge about the structure and replication cycle of PERVs in the context of retroviral infection risk.